2016
DOI: 10.1371/journal.pone.0162183
|View full text |Cite
|
Sign up to set email alerts
|

The Deficiency of Indoleamine 2,3-Dioxygenase Aggravates the CCl4-Induced Liver Fibrosis in Mice

Abstract: In the present study, we examined the role of indoleamine 2,3-dioxygenase (IDO) in the development of CCl4-induced hepatic fibrosis. The liver fibrosis induced by repetitive administration with CCl4 was aggravated in IDO-KO mice compared to WT mice. In IDO-KO mice treated with CCl4, the number of several inflammatory cells and the expression of pro-inflammatory cytokines increased in the liver. In the results, activated hepatic stellate cells (HSCs) and fibrogenic factors on HSCs increased after repetitive CCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Increased infiltration of immune cells and increased expression of proinflammatory cytokines was noticed in fibrotic livers of CCl 4 ‐treated IDO‐deficient mice. Aggravated liver fibrosis was also seen in mice that received IDO inhibitor, 1‐methyl‐ dl ‐tryptophan . In line with these findings, several clinical trials reported beneficent effects of MSCs in the therapy of cirrhosis .…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Increased infiltration of immune cells and increased expression of proinflammatory cytokines was noticed in fibrotic livers of CCl 4 ‐treated IDO‐deficient mice. Aggravated liver fibrosis was also seen in mice that received IDO inhibitor, 1‐methyl‐ dl ‐tryptophan . In line with these findings, several clinical trials reported beneficent effects of MSCs in the therapy of cirrhosis .…”
Section: Introductionsupporting
confidence: 60%
“…Protective and immuno‐modulatory role of IDO has been recently described in animal model of liver fibrosis induced by carbon tetra chloride (CCl 4 ) . Increased infiltration of immune cells and increased expression of proinflammatory cytokines was noticed in fibrotic livers of CCl 4 ‐treated IDO‐deficient mice.…”
Section: Introductionmentioning
confidence: 98%
“…Protective and immunomodulatory role of IDO has been recently described in CCl 4 ‐induced liver fibrosis . Increased infiltration of immune cells and increased expression of pro‐inflammatory cytokines was noticed in fibrotic livers of CCl 4 ‐treated IDO‐deficient mice.…”
Section: Discussionmentioning
confidence: 88%
“…Increased infiltration of immune cells and increased expression of pro‐inflammatory cytokines was noticed in fibrotic livers of CCl 4 ‐treated IDO‐deficient mice. Aggravated liver fibrosis was also seen in mice that received IDO inhibitor .…”
Section: Discussionmentioning
confidence: 92%
“…It is well documented that CCl 4 intoxication can induce liver lesion, cirrhosis and hepatocarcinoma [21,22], thus being a well-established model of liver damage. In the present study, CCl 4 administration increased the serum levels of ALT, AST, ALP.…”
Section: Discussionmentioning
confidence: 99%